Identitás és önevolúció - Mezei, Tamás (Acta Scientiarum Socialium, 2014)
Identity and self-evolution. This paper is focusing on the definition of an essential principium – personal identity – as it is constructed in Harris’s interpretation of the problem of human enhancement. It is examining Harris’s line of thought as the grammatical application, and the context of the notion identity unfolds, however, draw up some brief reflections on the viewpoints of others involved in the philosophical debate. The analysis denotes the most important deficiencies of the concept of identity by Harris, furthermore reveals the inconsistencies of the argumentation regarding the enhancing evolution in the context of the plural democracy. To conclude, Harris’s alternative to solve the hard moral problem of human enhancement does not provide us any real option, although, his concept of liberty, unreal foundation, and radical use of traditional ideas are rather original.
Keywords: enhancement; biotechnology; identity; oriented evolution